Comparison of operative outcome of open versus laparoscopic inguinal hernia in rural tertiary care hospital in Haryana: A randomized controlled study - Sanjeev Singla,; Pranav Bansal,; Garima Dwivedi,; Madhan Pranesh R,; Chanderbhan, (Asian Journal of Medical Sciences, 2024)
Background: Hernia surgery is one of the commonly done procedures in General surgery. A hernia is defined as an abnormal protrusion of an organ or tissue through a defect in its surrounding walls. Aims and Objectives: Comparison of morbidity in terms of total analgesic usage, mean length of hospital stay, comparison among open and TEP repair of hernias in primary inguinal hernias among males. Material and Methods: This study was done on 80 patients with clinical diagnosis of primary inguinal hernia over a period of one year to compare the result of two surgeries, open lichenstein repair (n=40) and TEP repair (n=40). Results: Postoperative pain using VAS was found to be lower in patients having laparoscopic TEP hernia repair when compared to open lichenstein tension free repair (p <0.01). Operating time was observed to be more with TEP group with mean of 59 ± 17.02 minutes compared with open group which had mean of 44.92±12 minutes. Mean number of analgesic in open cases was 6.65 ± 1.81 whereas in case of TEP group it was 4.35±1.47 over a period of one month. Conclusion: Lichtenstein tension free mesh hernioplasty still remains the gold standard operation done for inguinal hernia. TEP repair has proven to be superior in terms of perioperative hemorrhage and post-operative analgesia requirement. Study concluded that laparoscopic TEP repair of inguinal repair have a considerable clinical advantage over open hernia repair in terms of postoperative pain and analgesia requirement, hospital stay and postoperative complications.